A Case of Scopulariopsis brevicaulis Endocarditis with Mycotic Aneurysm in an Immunocompetent Host - Cawcutt, Kelly (Case Rep Med, 2015)
Scopulariopsis is a genus of mold that is usually associated with onychomycosis and rarely causes complicated infection in immunocompetent persons. We describe a case of an immunocompetent 65-year-old male with a history of mitral valve repair with prosthetic ring placement who developed acute left posterior knee pain. Imaging showed a left popliteal artery aneurysm and thrombus, and further evaluation with transesophageal echocardiogram demonstrated two large, mobile mitral valve vegetations. He underwent debridement and replacement of the mitral valve, followed by debridement of the left popliteal artery with peroneal artery bypass. The intraoperative cultures grew Scopulariopsis brevicaulis. Due to the resistant nature of the organism, he was initially treated with combination antifungals including liposomal amphotericin B, caspofungin, and voriconazole and was continued on chronic suppression with posaconazole with no evidence of recurrence. Scopulariopsis is a rare cause of fungal endocarditis. Treatment of Scopulariopsis endocarditis is challenging and is not well understood due to its rarity.